2011
DOI: 10.1098/rspb.2011.0880
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between warning signal efficacy and mating success in the wood tiger moth

Abstract: The coloration of species can have multiple functions, such as predator avoidance and sexual signalling, that directly affect fitness. As selection should favour traits that positively affect fitness, the genes underlying the trait should reach fixation, thereby preventing the evolution of polymorphisms. This is particularly true for aposematic species that rely on coloration as a warning signal to advertise their unprofitability to predators. Nonetheless, there are numerous examples of aposematic species show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
182
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(189 citation statements)
references
References 52 publications
4
182
3
Order By: Relevance
“…Understanding warning signal diversity in aposematic organisms continues to be a main focus in evolutionary biology as a way of studying natural selection and interactions among selective forces (Nokelainen et al 2012). Our findings support the hypothesis that predation is a selective force acting on the observed polytypism in Oophaga pumilio, and substantiate recent work suggesting that coloration functions as an honest signal toward predators (see Maan and Cummings 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Understanding warning signal diversity in aposematic organisms continues to be a main focus in evolutionary biology as a way of studying natural selection and interactions among selective forces (Nokelainen et al 2012). Our findings support the hypothesis that predation is a selective force acting on the observed polytypism in Oophaga pumilio, and substantiate recent work suggesting that coloration functions as an honest signal toward predators (see Maan and Cummings 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Paradoxically, withinpopulation variation exists in some aposematic species [5,6]. Despite studies suggesting a natural-sexual selection interaction as a cause [5,7], the mechanisms by which within-population variation is maintained, and its ecological and behavioural correlates, are poorly understood. Attempts to explain the maintenance of variable aposematic signals have primarily addressed among-population variation [8,9] or involved laboratory studies with artificial prey or computer games.…”
Section: Introductionmentioning
confidence: 99%
“…Because this relies on predators learning and remembering the relationship between colour patterns and unprofitability, selection should favour colour patterns with little or no variation [2]; patterns with low variation are easier to learn [2,3] and remember [4]. Paradoxically, withinpopulation variation exists in some aposematic species [5,6]. Despite studies suggesting a natural-sexual selection interaction as a cause [5,7], the mechanisms by which within-population variation is maintained, and its ecological and behavioural correlates, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanistic explanation for the increased predation risk of more melanized individuals is that the amount of color (yellow or white) decreases as the proportion of the hindwing covered by melanin increases. Nokelainen et al (2012) showed that both yellow and white pigments in the hindwings of male P. plantaginis serve as warning signals, even though yellow males were avoided more by avian predators than white males. Larger warning signals increase detection by predators (Bohlin et al 2008, Lindstedt et al 2008, which should enhance signal recognition and avoidance by predators (Lindström et al 1999a.…”
Section: Thermoregulation and Its Geographic Effect (Ii)mentioning
confidence: 99%